Mindfulness Community Education for High School Students and Guidance and Counseling Teachers - Yanti Ivana Suryanto; Lucas Nando Nugraha (Journal of Innovation and Community Engagement, 2022)
Some events that occur in a adolescence's life can be a source of stress. Stress could cause physical and psychological disorders. Stress resilience allows a person to avoid the negative effects of stress. Objective of this community education activity was to provide initial information about mindfulness as a way of self-empowerment to improve stress resilience of high school students and identify the resilience level to determine the need for further training. The participants in this activity were high school students and guidance-and-counseling teachers. Education about mindfulness were given to high school students and guidance-and-counseling teachers through online meeting platform. Before the education session, participants were asked to voluntarily fill out a Brief Resilience Scale questionnaire to identify the participants' level of stress resilience. At the end of the education, a mindfulness practice session was given. Identification of stress resilience showed that of the 277 participants who filled out the questionnaire, 27.2% had low resilience levels, 72.2% had normal resilience levels, and 0.4% had high resilience levels. The percentage of respondents with low resilience decreased with increasing age (31.5% in adolescents, 22.2% in young adults, and 10.2% in adults). In teacher’s group, 10.71%, 87.50%, and 10.71% of respondents had low, normal, and high resilience, respectively. In student’s group, 68.33% and 31.67% of respondents had normal and high resilience, respectively. A higher percentage of adolescents with low resilience require follow-up. This activity revealed the importance to increase stress resilience which have an impact on improving the learning quality, especially for adolescents as the nation's next generation.